1999
DOI: 10.1099/00207713-49-4-1925
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes of Saccharomyces sensu lato species

Abstract: An improved pulsed-f ield electrophoresis program was developed to study differently sized chromosomes within the genus Saccharomyces. The number of chromosomes in the type strains was shown to be nine in Saccharomyces castellii and Saccharomyces dairenensis, 12 in Saccharomyces servazzii and Saccharomyces unisporus, 16 in Saccharomyces exiguus and seven in Saccharomyces kluyveri. The sizes of individual chromosomes were resolved and the approximate genome sizes were determined by the addition of individual ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 25 publications
7
52
0
Order By: Relevance
“…A recent study showed at least 12 bands (570^1950 kb) for an estimated genome size of 12.3 Mb [8]. Similar patterns were obtained with S. unisporus isolates, consistent with the fact that these species are closely related [9].…”
Section: Introductionsupporting
confidence: 79%
“…A recent study showed at least 12 bands (570^1950 kb) for an estimated genome size of 12.3 Mb [8]. Similar patterns were obtained with S. unisporus isolates, consistent with the fact that these species are closely related [9].…”
Section: Introductionsupporting
confidence: 79%
“…Previous studies have shown that the species of Saccharomyces sensu stricto exhibit relatively homogeneous karyotypes compared with those of species of Saccharomyces sensu lato (Vaughan-Martini et al, 1993;Fischer et al, 2000;Naumov et al, 1992Naumov et al, , 1995Petersen et al, 1999;Lu et al, 2004;Wu & Bai, 2005). The electrophoretic karyotypes of strains H-6 T , ZX-15 and ZX-20 bore a superficial resemblance to those of the accepted Saccharomyces species, being consistent with their placement in this genus based on rDNA sequence analysis (Fig.…”
Section: Electrophoretic Karyotypingsupporting
confidence: 65%
“…The strain used in this work (type strain CBS3082) is diploid. Petersen et al [1] estimated that S. kluyveri contains seven chromosomes with a 10 Mb genome size, in agreement with Vaughan-Martini et al [2]. Weinstock and Strathern [3], however, observed eight separate chromosomal bands by pulsed ¢eld gel electrophoresis of strain CBS4568, all larger than 0.9 Mb.…”
Section: Introductionsupporting
confidence: 63%